Vibration-based damage detection in beam structures with multiple cracks: modal curvature vs. modal flexibility methods. Issue 1 (2nd January 2019) - Altunışık, Ahmet Can; Okur, Fatih Yesevi; Karaca, Sebahat; Kahya, Volkan
ABSTRACT: This study presents damage localisation in steel cantilever beams including multiple cracks based on changes in the modal curvature and flexibility. Natural frequencies and corresponding mode shapes of circular-hollow-sectional and box-sectional steel cantilever beams are obtained by analytical and experimental models under six damage scenarios. Based on these data, the modal curvature and modal flexibility methods are employed to localise the cracks within the beams. Comparisons are made to show effectiveness of the methods in determination of crack locations.